Morphology of diesel soot residuals from supercooled water droplets and ice crystals: implications for optical properties. (4th November 2015) - China, Swarup; Kulkarni, Gourihar; Scarnato, Barbara V; Sharma, Noopur; Pekour, Mikhail; Shilling, John E; Wilson, Jacqueline; Zelenyuk, Alla; Chand, Duli; Liu, Shang; Aiken, Allison C; Dubey, Manvendra; et al.
Abstract: Freshly emitted soot particles are fractal-like aggregates, but atmospheric processes often transform their morphology. Morphology of soot particles plays an important role in determining their optical properties, life cycle and hence their effect on Earth's radiative balance. However, little is known about the morphology of soot particles that participated in cold cloud processes. Here we report results from laboratory experiments that simulate cold cloud processing of diesel soot particles by allowing them to form supercooled droplets and ice crystals at −20 and −40 °C, respectively. Electron microscopy revealed that soot residuals from ice crystals were more compact (roundness ∼0.55) than those from supercooled droplets (roundness ∼0.45), while nascent soot particles were the least compact (roundness ∼0.41). Optical simulations using the discrete dipole approximation showed that the more compact structure enhances soot single scattering albedo by a factor up to 1.4, thereby reducing the top-of-the-atmosphere direct radiative forcing by ∼63%. These results underscore that climate models should consider the morphological evolution of soot particles due to cold cloud processing to improve the estimate of direct radiative forcing of soot.